Water-based hot melt adhesive and water-based hot melt adhesive coating medical paper
By forming a coating on medical paper through a water-based hot melt adhesive formula, the problem of insufficient or excessive sealing strength of medical packaging materials during the heat sealing process is solved, good air permeability and stability are achieved, the risk of fiber shedding and contamination is reduced, the production process is simplified and organic solvent residues are avoided.
Patent Information
- Application Number
- CN202410429221.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-10
- Publication Date
- 2025-10-17
AI Technical Summary
Existing medical packaging materials have problems with insufficient or excessive sealing strength during the heat sealing process, resulting in bag breakage or fiber shedding and contamination when torn. At the same time, it is difficult to strike a balance between good air permeability and production complexity, and traditional hot melt adhesives use organic solvents that may leave residual environmentally unfriendly residues.
It uses a water-based hot melt adhesive formula containing ethylene-vinyl acetate copolymer, ethylene-acrylic acid copolymer, water-based paraffin wax and powder wax. Water is used as a solvent to form a coating on medical paper, simplifying the production process, providing good sealing strength and air permeability, and stably breaking when peeling.
The invention can ensure that the sealing stability of medical packaging materials is maintained during steam or EO gas sterilization, reduce fiber shedding pollution, avoid organic solvent residue, and simplify the production process.
Smart Images

Figure BDA0004785075540000201 
Figure BDA0004785075540000211
Abstract
Description
TECHNICAL FIELD
[0001] The present invention relates to a water-based hot melt adhesive which can be used in hot melt coating of medical paper to achieve good sealing strength for heat sealing and not affect the air permeability required for medical product packaging materials. BACKGROUND
[0002] The main purpose of medical product packaging materials is to provide a bacteria-proof environment for medical products during transportation or before use, so that the medical devices can maintain the sterile state after sterilization before use. Generally, medical products are sterilized after packaging, and the sterilization process can be divided into steam sterilization, EO sterilization and radiation sterilization. In response to different sterilization methods, different medical packaging materials are used. For example, for EO sterilization and steam sterilization, the material needs to have excellent gas permeability to ensure that water vapor or EO gas can effectively pass through the packaging bag and sterilize the internal medical devices. In the prior art, materials with good microbial barrier effect and air permeability, such as medical paper, are widely used as medical product packaging materials.
[0003] Medical product packaging materials are usually packaged by heat sealing, which involves coating a hot seal adhesive on medical paper and then heat sealing the four edges with plastic film or blister packaging to obtain the medical product packaging material. In addition to good air permeability, the medical product packaging material must also have good heat sealing strength and peelable properties. Insufficient heat sealing strength will result in poor sealing of the medical product packaging, which may cause bag rupture during sterilization due to high gas pressure. However, too high heat sealing strength will make it difficult for the user to tear open the packaging or cause contamination of the medical product due to dust adhering to the medical product when tearing the packaging.
[0004] The hot melt adhesive used for the breathable material for medical product packaging is generally sealed by hot melt adhesive. The traditional hot melt adhesive formula is to melt and mix thermoplastic resin, tackifier, wax, filler, plasticizer, antioxidant and additive, and then to be molded into granular, strip, sheet and film, and then to be processed by hot pressing or hot melting. The process is relatively complex. For example, CN108587521A discloses a water-based coating hot seal adhesive for medical dialysis paper, which is prepared by stirring and emulsifying thermoplastic resin, resin tackifier, wax, emulsifier and additive at 120℃ to form a hot melt adhesive coating liquid, and then coated on the medical paper to form a hot seal layer. The seal layer provides high adhesion, but the tear strength of the medical paper is low, which can easily cause the medical packaging to tear and damage, and can cause the medical paper to fall and pollute the medical materials. In CN110591602A, a face adhesive and a bottom adhesive are coated on the medical blister box hot seal material, and the adhesion between the face adhesive and the bottom adhesive is lower than that between the face adhesive and the packaging material, so as to maintain the adhesion between the medical seal material and the blister box, but it is not easy to tear the hot seal material. However, this requires two layers of adhesive, which increases the inconvenience of production. In addition, CN108441149A discloses a two-stage method for preparing a hot melt adhesive coating liquid for the hot seal layer of medical packaging material. The hot melt adhesive powder is prepared by melting and mixing thermoplastic resin, resin tackifier and wax at a temperature higher than 160℃, and then dispersing the powder in a polyacrylic acid emulsion by emulsifier to form a coating. The two-stage manufacturing method increases the complexity of production. In addition, the existing hot seal adhesive uses organic solvents to mix thermoplastic resin, resin tackifier and wax, which may remain on the medical product packaging and is not environmentally friendly. SUMMARY
[0005] The present application provides a water-based hot melt adhesive for medical packaging material, which can form a coating on the medical paper to maintain good breathability after the medical paper is sealed with a flexible sheet or a blister container for steam sterilization and EO gas sterilization process and maintain the stability of the seal. The water-based hot melt adhesive of the present application can eliminate the mixing step of traditional hot melt adhesive, and can achieve the required sealing strength and specific breathability of medical packaging material after application. In addition, when the medical packaging material prepared by the water-based hot melt adhesive of the present application is peeled off from the sealed part, the water-based hot melt adhesive coating can be stably broken, so as to reduce the pollution problem of medical equipment caused by the falling of medical paper fibers.
[0006] The water-based hot melt adhesive disclosed in the present application can contain 25-70 parts by weight of ethylene-vinyl acetate copolymer, 5-20 parts by weight of ethylene-acrylic acid copolymer, 6.5-55 parts by weight of water-based paraffin wax and 5-15 parts by weight of powder wax, wherein the particle size of the powder wax is less than 8 microns.
[0007] In one embodiment of the present application, the water-based hot melt adhesive preferably comprises 30 to 68 parts by weight of the ethylene-vinyl acetate copolymer, 6 to 18 parts by weight of the ethylene-acrylic acid copolymer, 7 to 52 parts by weight of the water-based paraffin wax, and 7 to 13 parts by weight of the powder wax.
[0008] In one embodiment of the present application, the ratio of the weight of the powder wax to the sum of the weights of the ethylene-vinyl acetate copolymer and the ethylene-acrylic acid copolymer is 0.09 to 2.1.
[0009] In one embodiment of the present application, the ethylene-vinyl acetate copolymer has a glass transition temperature of -40 to 10°C and a melting point of 200 to 300°C.
[0010] In one embodiment of the present application, the ethylene-acrylic acid copolymer has a glass transition temperature of 0 to 10°C and a melting point of 70 to 110°C.
[0011] In one embodiment of the present application, the powder wax has a glass transition temperature of less than 0°C and a melting point of 70 to 180°C.
[0012] In one embodiment of the present application, the powder wax is selected from the group consisting of Fischer-Tropsch synthesis powder wax, polypropylene powder wax, polyethylene powder wax, oxidized polyethylene powder wax, microcrystalline wax, and combinations thereof.
[0013] In one preferred embodiment of the present application, the powder wax has a particle size of 2 to 7 microns.
[0014] In one embodiment of the present application, the water-based paraffin wax has a glass transition temperature of -120 to -50°C and a melting point of 30 to 65°C.
[0015] In another embodiment of the present application, the water-based hot melt adhesive optionally further comprises a water-based polyolefin resin, and the water-based polyolefin resin is a hydrophilically modified polyolefin, a water-based ionic polymer, or a combination thereof.
[0016] In another embodiment of the present application, the water-based hot melt adhesive further comprises 3 to 10 parts by weight of the water-based polyolefin resin.
[0017] In another embodiment of the present application, the hydrophilically modified water-based polyolefin is selected from the group consisting of a hydrophilically modified polyethylene resin, a hydrophilically modified polypropylene resin, a hydrophilically modified polybutene resin, a hydrophilically modified oxidized polyethylene resin, and combinations thereof.
[0018] In another embodiment of the present application, the water-based ionic polymer is selected from the group consisting of a water-based polyethylene ionic polymer, a water-based polypropylene ionic polymer, a water-based polybutene ionic polymer, a water-based oxidized polyethylene ionic polymer, and combinations thereof.
[0019] In another embodiment of the present application, the weight ratio of the aqueous polyolefin resin and the aqueous paraffin is 1:1 to 1:3.
[0020] The present application further provides an aqueous hot melt adhesive coated medical paper, which comprises a medical paper and an aqueous hot melt adhesive coating formed on at least one surface of the medical paper, wherein the aqueous hot melt adhesive coating comprises 25 to 70 parts by weight of an ethylene-vinyl acetate copolymer, 5 to 20 parts by weight of an ethylene-acrylic acid copolymer, 6.5 to 55 parts by weight of an aqueous paraffin, and 5 to 15 parts by weight of a powder wax, wherein the particle size of the powder wax is less than 8 microns.
[0021] In an embodiment of the aqueous hot melt adhesive coated medical paper of the present application, the air permeability of the aqueous hot melt adhesive coated medical paper is less than 600 seconds and the seal strength is greater than 300 g / 15 mm.
[0022] In an embodiment of the aqueous hot melt adhesive coated medical paper of the present application, the coating amount of the aqueous hot melt adhesive on the medical paper is 1 g / m 2 to 5 g / m 2 .
[0023] The above summary is intended to provide a simplified outline of the present disclosure to convey to the reader the basic understanding of the present disclosure. The summary is not a complete overview of the present disclosure, and its purpose is not to identify important / critical elements of the embodiments of the present application or to define the scope of the present application. After reading the following embodiments, those skilled in the art can easily understand the basic spirit of the present application and the technical means and embodiments employed by the present application. DETAILED DESCRIPTION
[0024] In order to make the description of the present disclosure more detailed and complete, the following describes the embodiments and specific examples of the present application; however, this is not the only form of implementing or using the embodiments of the present application. The embodiments disclosed below can be combined with each other or replaced by each other in a beneficial case, and other embodiments can be added in an embodiment without further description or illustration.
[0025] The advantages, features and achieved technical methods of the present application will be described in more detail and more easily understood with reference to the exemplary embodiments, and the present application or can be realized in different forms, so it should not be understood as being limited to the embodiments described herein. On the contrary, those skilled in the art will provide embodiments to make the present disclosure more thorough and complete and to fully convey the scope of the present application, and the present application will be limited only by the appended claims.
[0026] Unless otherwise defined, all terms (including technical and scientific terms) used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application belongs. By way of example, and not limitation, such terms as generally defined, for example, in commonly used dictionaries should be interpreted as having a meaning that is consistent with their meaning in the context of the relevant art and will not be interpreted in an overly idealized or formal sense unless clearly defined herein.
[0027] The present application provides a water-based hot melt adhesive for medical paper, which forms a coating on the medical paper and provides good air permeability and reliable sealing strength and peelability after periphery sealing with a flexible sheet or a blister container. When the sealed portion is peeled, the water-based hot melt adhesive coating is stably broken, thereby reducing contamination of medical devices due to fiber shedding of the medical paper.
[0028] The present application provides a water-based hot melt adhesive for medical packaging material, which includes 25 to 70 parts by weight of ethylene-vinyl acetate copolymer, 5 to 20 parts by weight of ethylene-acrylic acid copolymer, 6.5 to 55 parts by weight of water-based paraffin, and 5 to 15 parts by weight of powder wax, wherein the powder wax has a particle size of less than 8 micrometers.
[0029] The water-based hot melt adhesive of the present application can be coated on the surface of medical paper for medical packaging after adding water as a solvent, and a water-based hot melt adhesive coating medical paper is produced after removing the solvent by heating. The water-based hot melt adhesive coating formed on the medical paper can be directly subjected to a heat sealing process at 90 to 150°C. The water-based hot melt adhesive of the present application can eliminate the mixing step required for conventional hot melt adhesives. In addition, since water is used as a solvent, the problems of organic solvent residues in medical packaging materials and environmental unfriendliness due to the use of organic solvents in known hot melt adhesives can be avoided.
[0030] The water-based hot melt adhesive coating medical paper produced using the water-based hot melt adhesive of the present application can provide good air permeability, and thus can be subjected to a steam sterilization or EO gas sterilization process after periphery heat sealing of the water-based hot melt adhesive coating medical paper with a flexible sheet or a blister container. In addition, the water-based hot melt adhesive of the present application can provide good heat sealing properties and peelability, and the medical packaging material produced using the same can have the required heat sealing strength, and when the packaging material is torn, the packaging material is stably broken at the water-based hot melt adhesive coating, thereby reducing contamination of medical devices due to fiber shedding of the medical paper.
[0031] In a preferred embodiment of the present application, the water-based hot melt adhesive preferably includes 30 to 68 parts by weight of ethylene-vinyl acetate copolymer, 6 to 18 parts by weight of ethylene-acrylic acid copolymer, 7 to 52 parts by weight of water-based paraffin, and 7 to 13 parts by weight of powder wax.
[0032] The ethylene-vinyl acetate copolymer used in the water-based hot melt adhesive of the present application has a glass transition temperature (Tg) of -40 to 10°C and a melting point of 200 to 300°C. The ethylene-vinyl acetate copolymer suitable for the water-based hot melt adhesive of the present application can be commercially available, such as DA-104 from Dalian Chemical, EP-645, EAF-68, EP 701K, EP 707K from Wacker, Germany, Celvolit 1498, Celvolit 1475 from Celanese, USA, etc., but is not limited thereto.
[0033] The ethylene-acrylic acid copolymer used in the water-based hot melt adhesive of the present application has a glass transition temperature (Tg) of 0 to 10°C and a melting point of 70 to 110°C. The ethylene-acrylic acid copolymer suitable for the water-based hot melt adhesive of the present application can be commercially available, such as 5132, 5322 from Allinova, Netherlands, 3644N, 3624 from Eurika, Belgium, 498340R from Michelman, USA, CER 1061 from BYK, Germany, etc., but is not limited thereto.
[0034] The water-based hot melt adhesive of the present application uses ethylene-vinyl acetate copolymer and ethylene-acrylic acid copolymer as the hot melt adhesive matrix, and the water-based hot melt adhesive coating formed thereby has high adhesion to medical paper. By adding water-based paraffin, the water-based hot melt adhesive coating formed thereby has high peelability when the medical paper is heat-sealed to a flexible packaging material such as a polyethylene or polypropylene substrate, etc., because the melting point of the water-based paraffin is low. Therefore, the problem of fiber shedding when the medical paper is torn can be reduced.
[0035] The water-based paraffin used in the water-based hot melt adhesive of the present application has a glass transition temperature (Tg) of -120 to -50°C and a melting point of 30 to 65°C. The water-based paraffin suitable for the water-based hot melt adhesive of the present application can be commercially available, such as P50 from Allinova, Netherlands, AQUACER 497, AQUACER 539 from BYK, Germany, etc., but is not limited thereto. When the amount of water-based paraffin used is too much, the sealing strength of the medical packaging material will be reduced. When the amount of water-based paraffin used is too little, the problem of fiber shedding of the medical paper when the heat-sealed portion is peeled will occur.
[0036] The powder wax of the water-based hot melt adhesive of the present application is used to reduce the melt viscosity and surface tackiness of the water-based hot melt adhesive, and to adjust the flowability and wettability of the hot melt adhesive, but without significantly reducing the adhesive properties of the water-based hot melt adhesive. Furthermore, to help the coating layer formed by the water-based hot melt adhesive of the present application on the medical paper to have good air permeability and peelability, the particle size (D50) of the powder wax is less than 8 microns (μm), and preferably between 2 microns (μm) and 7 microns (μm). When the particle size of the powder wax is too large, the medical paper fibers will fall off when the medical packaging material is peeled off at the heat-sealed portion. When the particle size of the powder wax is too small, the air permeability of the hot melt adhesive coating layer will be poor.
[0037] The powder wax suitable for the water-based hot melt adhesive of the present application has a glass transition temperature (Tg) of less than 0°C, and a melting point of between 70°C and 180°C. The powder wax used in the present application is selected from the group consisting of commercially available Fischer-Tropsch synthetic powder wax, polypropylene powder wax, polyethylene powder wax, oxidized polyethylene powder wax, microcrystalline wax, and combinations thereof, but is not limited thereto. The suitable Fischer-Tropsch synthetic powder wax may, for example, be Sasolwax Spray 30-G, Spray 30G-M, Spray 30G-EF, Spray 105, Spray 105-G, Spray 105G-EF, Sasolwax Aqua 30-G, Aqua 30G-EF, etc. obtained from Sasol Chemicals Pacific Co., Ltd. of South Africa. The suitable polypropylene powder wax may, for example, be BYK®-Wax MP 2120, etc. obtained from BYK-Chemie GmbH of Germany. The suitable polyethylene powder wax may, for example, be BYK®-Wax 929N, etc. obtained from BYK-Chemie GmbH of Germany. The suitable oxidized polyethylene powder wax may, for example, be Münzing®-Wax MO 4715, etc. obtained from Münzing Chemie GmbH of Germany, but is not limited thereto. 913、 914、The suitable Fischer-Tropsch synthetic powder wax may, for example, be Sasolwax Spray 30-G, Spray 30G-M, Spray 30G-EF, Spray 105, Spray 105-G, Spray 105G-EF, Sasolwax Aqua 30-G, Aqua 30G-EF, etc. obtained from Sasol Chemicals Pacific Co., Ltd. of South Africa. The suitable polypropylene powder wax may, for example, be BYK®-Wax MP 2120, etc. obtained from BYK-Chemie GmbH of Germany. The suitable polyethylene powder wax may, for example, be BYK®-Wax 929N, etc. obtained from BYK-Chemie GmbH of Germany. The suitable oxidized polyethylene powder wax may, for example, be Münzing®-Wax MO 4715, etc. obtained from Münzing Chemie GmbH of Germany, but is not limited thereto. MP2120, etc. obtained from BYK-Chemie GmbH of Germany. The suitable polyethylene powder wax may, for example, be BYK®-Wax 929N, etc. obtained from BYK-Chemie GmbH of Germany. The suitable oxidized polyethylene powder wax may, for example, be Münzing®-Wax MO 4715, etc. obtained from Münzing Chemie GmbH of Germany, but is not limited thereto. 925、 929N, etc. obtained from BYK-Chemie GmbH of Germany. The suitable polyethylene powder wax may, for example, be BYK®-Wax 929N, etc. obtained from BYK-Chemie GmbH of Germany. The suitable oxidized polyethylene powder wax may, for example, be Münzing®-Wax MO 4715, etc. obtained from Münzing Chemie GmbH of Germany, but is not limited thereto. MO4715, etc. obtained from Münzing Chemie GmbH of Germany, but is not limited thereto.
[0038] In an embodiment of the present application, the ratio of the weight of the powder wax to the sum of the weights of the ethylene-vinyl acetate copolymer and the ethylene-acrylic acid copolymer can be between 0.09 and 2.1. If the amount of powder wax used is too small, the air permeability of the hot melt adhesive coating layer will be insufficient. If the total amount of powder wax is too large, the sealing strength of the medical packaging material will be too low.
[0039] In another embodiment of the present application, the water-based hot melt adhesive optionally further comprises a water-based polyolefin resin to improve the heat sealing strength. The water-based polyolefin resin is a hydrophilically modified water-based polyolefin, a water-based ionomer, or a combination thereof.
[0040] The hydrophilic modified polyolefin can be a polyolefin modified with an unsaturated carboxylic acid or an acid anhydride thereof, for example, introducing carboxyl or acid anhydride group to the polyolefin, or adding a surfactant to the polyolefin resin. The glass transition temperature (Tg) of the hydrophilic modified polyolefin that can be used in the water-based hot melt adhesive of the present application can be less than 0℃ and the melting point can be higher than 90℃, preferably, the glass transition temperature (Tg) can be less than -100℃ and the melting point can be higher than 120℃. The suitable hydrophilic modified polyolefin is selected from the group consisting of a hydrophilic modified polyethylene resin, a hydrophilic modified polypropylene resin, a hydrophilic modified polybutene resin, a hydrophilic modified oxidized polyethylene resin, and combinations thereof. The aforementioned hydrophilic modified polyolefin can be commercially available, for example, ALTRIX WPE-09838 from Kolon Chemical, SB-1030N from Unitika arrowbase, HME-118-B from MICA, etc., but is not limited thereto.
[0041] The water-based ionic polymer that can be used in the water-based hot melt adhesive of the present application refers to a polymer in which a copolymer of ethylene and (meth)acrylic acid is used as a main chain and metal ions are introduced thereon to crosslink molecules by ionic bonds. The suitable water-based ionic polymer has a glass transition temperature (Tg) of less than 0℃ and a melting point of higher than 80℃, preferably, a glass transition temperature (Tg) of less than -100℃ and a melting point of higher than 85℃. The aforementioned water-based ionic polymer is selected from the group consisting of a water-based polyethylene ionic polymer, a water-based polypropylene ionic polymer, a water-based polybutene ionic polymer, a water-based oxidized polyethylene ionic polymer, and combinations thereof. The suitable water-based ionic polymer can be commercially available, for example, CHEMIPEARL TM S300, S500, or EVOQUE from DuPont The thermoplastic ionic resin, but is not limited thereto.
[0042] In another embodiment of the present application, the water-based hot melt adhesive selectively further comprises 3 to 10 parts by weight of the water-based polyolefin resin. The weight ratio of the water-based polyolefin resin and the water-based paraffin is 1:1 to 1:3. When the amount of the water-based polyolefin resin is too much, the medical paper fibers can be peeled off when the medical packaging material is peeled at the heat-sealed portion.
[0043] The water-based hot melt adhesive disclosed in the present application can further comprise other additives, for example, a wetting dispersant, a defoaming agent, a thickening agent, etc. for improving the coating processability of the water-based hot melt adhesive; an antioxidant, an ultraviolet (UV) stabilizer, an antibacterial agent, an antistatic agent, etc. for increasing the functionality of the water-based hot melt adhesive. The types and amounts of such additives can be selected by those skilled in the art as needed.
[0044] The present application also provides a water-based hot melt adhesive coated medical paper, which comprises a medical paper and a water-based hot melt adhesive coating formed on at least one surface of the medical paper, wherein the water-based hot melt adhesive coating comprises 25-70 parts by weight of an ethylene-vinyl acetate copolymer, 5-20 parts by weight of an ethylene-acrylic acid copolymer, 6.5-55 parts by weight of a water-based paraffin wax, and 5-15 parts by weight of a powder wax, wherein the particle size of the powder wax is less than 8 microns. The water-based hot melt adhesive coated medical paper has an air permeability of less than 600 seconds (TAPPI (Technical Association of the Pulp and Paper industry) T-460) and a seal strength of greater than 300 g / 15 mm (ASTM (American Society for Testing and Materials) F-88).
[0045] The "seal strength" referred to herein means the pulling force required to separate two sealed sheets, which is measured in a "T-separation" test according to ASTM F88 at a pulling speed of 200 mm / min.
[0046] The "air permeability" referred to herein means the air resistance of a gas passing through an air permeable sheet, which is measured according to the TAPPI T-460 standard as the air resistance of 100 cc. gas passing through an area of about 1 square inch in a circular shape at a pressure difference of 1.22 kPa.
[0047] The medical paper suitable for use in the water-based hot melt adhesive coated medical paper of the present application can be any medical paper commonly used in medical packaging, such as Pelta Med PurePeel EO of Pelta Medical Papers in the UK or Ethypel Classic of STERIMED in France, but is not limited thereto.
[0048] The water-based hot melt adhesive coating of the water-based hot melt adhesive coated medical paper of the present application has a coating amount of 1 g / m 2 to 5 g / m 2 on the medical paper. In detail, the water-based hot melt adhesive coating can be uniformly coated on the entire surface of the medical paper or locally coated on a specific area, and the coating amount is 1 g / m 2 to 5 g / m 2 , preferably 2 g / m 2 to 4 g / m 2 .
[0049] The packaging substrate suitable for sealing with the water-based hot melt adhesive coated medical paper of the present application can be, for example, polyethylene terephthalate (PET), polyvinyl chloride (PVC), polystyrene (PS), polypropylene (PP), polyethylene (PE), polycarbonate (PC), Nylon film or a blister hard substrate, but is not limited thereto.
[0050] The water-based hot melt adhesive coated medical paper of the present application can be heat sealed with another packaging substrate, such as the aforementioned packaging substrate, at a temperature of 90 to 150°C, and the sealing strength after sealing is greater than 300 g / 15 mm, preferably greater than 350 g / 15 mm.
[0051] The method for preparing the water-based hot melt adhesive coated medical paper disclosed in the present application comprises adding ethylene-acrylic acid copolymer, water-based paraffin, powder wax and water as a solvent into ethylene-vinyl acetate copolymer, and fully stirring and dispersing to form a water-based hot melt adhesive emulsion. The prepared water-based hot melt adhesive emulsion can be coated on a medical paper, and dried at a temperature of 80 to 120°C to remove the solvent to form a water-based hot melt adhesive coated medical paper. The coating method of the water-based hot melt adhesive can use, for example, roll coating, knife coating, roller coating, spin coating, spraying, slot coating, air knife coating and other coating methods commonly used in this technical field, but is not limited thereto.
[0052] The water-based hot melt adhesive coated medical paper of the present application has good air permeability after heat sealing with a flexible sheet or a blister container at the periphery, which facilitates the steam sterilization or EO gas sterilization process, and can provide reliable sealing strength and peelability, so that when the sealed part of the heat sealing is peeled off, the water-based hot melt adhesive layer can be stably separated, thereby reducing the problem of contamination of medical devices caused by fiber shedding of the medical paper.
[0053] The following examples are used to further illustrate the present application, but the content of the present application is not limited thereto.
[0054] Example
[0055] The materials used in the examples of the present application are as follows:
[0056] DA-104: ethylene-vinyl acetate copolymer emulsion, melting point 240°C, glass transition temperature (Tg) -10 to -20°C, solid content 55%, solvent water, purchased from Dalian Chemical Industry Co., Ltd.
[0057] EP 707K: Ethylene-vinyl acetate copolymer emulsion, melting point greater than 250°C, glass transition temperature (Tg) of 7°C, solid content of 55%, solvent is water, available from Wacker Chemie AG, Germany.
[0058] Novaseal 5132: Ethylene-acrylic acid copolymer emulsion, melting point of 89 to 103°C, solid content of 32%, solvent is water, available from Allinova B.V., Netherlands.
[0059] Aquacer 497: Waterborne paraffin wax emulsion, melting point of 60°C, solid content of 50%, solvent is water, available from BYK, Germany.
[0060] W400: Polyethylene powder wax emulsion, melting point of 90°C to 100°C, average particle size of 5 μιη, solid content of 40%, solvent is water, available from Mitsui Chemicals, Japan.
[0061] W410: Polyethylene powder wax emulsion, melting point of 90°C to 110°C, average particle size of 9 μιη, solid content of 40%, solvent is water, available from Mitsui Chemicals, Japan.
[0062] Wax 4: Polyethylene powder wax emulsion, melting point of 110°C, average particle size of 4 μιη, solid content of 40%, solvent is water, available from BASF, Germany.
[0063] CHEMIPEARL TM S300: Polyethylene ionic polymer emulsion, melting point of 96°C, glass transition temperature (Tg) of -120°C, solid content of 35%, solvent is water, available from Mitsui Chemicals, Inc., Japan.
[0064] CHEMIPEARL TM S500: Polyethylene ionic polymer emulsion, melting point of 89°C, glass transition temperature (Tg) of -120°C, solid content of 42%, solvent is water, available from Mitsui Chemicals, Inc., Japan.
[0065] EW-NA: Thickener, available from Elementis plc, United Kingdom.
[0066] AS-1125: Thickener, available from Cognis GmbH, Germany.
[0067] PeltaMed PurePeelEO 60gsm: Medical paper (60g), available from PELTA MEDICAL PAPERS, UK.
[0068] Example 1
[0069] After mixing and stirring 233.3 parts by weight of ethylene-vinyl acetate copolymer emulsion (DA-104), 100 parts by weight of ethylene-acrylic acid copolymer emulsion (Novaseal 5132), 29.3 parts by weight of water-based paraffin emulsion (Aquacer 497), 50 parts by weight of polyethylene powder wax emulsion (W400), 2.9 parts by weight of thickener (EW-NA), and 370.4 parts by weight of deionized water for 30 minutes to uniformly disperse, an aqueous hot melt adhesive solution was formed.
[0070] The aqueous hot melt adhesive solution was coated on the medical paper (PeltaMed PurePeelEO 60gsm) and dried at 100°C for 2 minutes to form an aqueous hot melt adhesive coating layer on the medical paper, thereby preparing an aqueous hot melt adhesive coating medical paper.
[0071] The obtained aqueous hot melt adhesive coating medical paper was subjected to air permeability test, heat seal strength test, and peel test according to the methods described below, and the test results are shown in Table 1 below.
[0072] Example 2
[0073] After mixing and stirring 233.3 parts by weight of ethylene-vinyl acetate copolymer emulsion (DA-104), 100 parts by weight of ethylene-acrylic acid copolymer emulsion (Novaseal 5132), 29.3 parts by weight of water-based paraffin emulsion (Aquacer 497), 50 parts by weight of polyethylene powder wax emulsion (W400), 2.9 parts by weight of thickener (EW-NA), and 370.4 parts by weight of deionized water for 30 minutes to uniformly disperse, an aqueous hot melt adhesive solution was formed.
[0074] The aqueous hot melt adhesive solution was coated on the medical paper (PeltaMed PurePeelEO 60gsm) and dried at 100°C for 2 minutes to form an aqueous hot melt adhesive coating layer on the medical paper, thereby preparing an aqueous hot melt adhesive coating medical paper.
[0075] The obtained aqueous hot melt adhesive coating medical paper was subjected to air permeability test, heat seal strength test, and peel test according to the methods described below, and the test results are shown in Table 1 below.
[0076] Example 3
[0077] An aqueous hot melt adhesive solution was formed by mixing and stirring 233.3 parts by weight of ethylene-vinyl acetate copolymer latex (DA-104), 100 parts by weight of ethylene-acrylic acid copolymer latex (Novaseal 5132), 333.3 parts by weight of aqueous paraffin emulsion (Aquacer 497), 93.3 parts by weight of polyethylene powder wax emulsion (W400), 5.2 parts by weight of thickener (EW-NA), and 708.1 parts by weight of deionized water for 30 minutes to uniformly disperse them.
[0078] The aqueous hot melt adhesive solution was coated on a medical paper (PeltaMed PurePeelEO 60gsm) and dried at 100°C for 2 minutes to form an aqueous hot melt adhesive coating layer on the medical paper, thereby preparing an aqueous hot melt adhesive coating medical paper.
[0079] The obtained aqueous hot melt adhesive coating medical paper was subjected to air permeability test, heat seal strength test, and peel test according to the methods described below, and the test results are shown in Table 1 below.
[0080] Example 4
[0081] An aqueous hot melt adhesive solution was formed by mixing and stirring 233.3 parts by weight of ethylene-vinyl acetate copolymer latex (DA-104), 100 parts by weight of ethylene-acrylic acid copolymer latex (Novaseal 5132), 333.3 parts by weight of aqueous paraffin emulsion (Aquacer 497), 93.3 parts by weight of polyethylene powder wax emulsion (W400), 5.2 parts by weight of thickener (EW-NA), and 708.1 parts by weight of deionized water for 30 minutes to uniformly disperse them.
[0082] The aqueous hot melt adhesive solution was coated on a medical paper (PeltaMed PurePeelEO 60gsm) and dried at 100°C for 2 minutes to form an aqueous hot melt adhesive coating layer on the medical paper, thereby preparing an aqueous hot melt adhesive coating medical paper.
[0083] The obtained aqueous hot melt adhesive coating medical paper was subjected to air permeability test, heat seal strength test, and peel test according to the methods described below, and the test results are shown in Table 1 below.
[0084] Example 5
[0085] An aqueous hot melt adhesive solution was formed by mixing and stirring 233.3 parts by weight of ethylene-vinyl acetate copolymer latex (DA-104), 100 parts by weight of ethylene-acrylic acid copolymer latex (Novaseal 5132), 660 parts by weight of aqueous paraffin emulsion (Aquacer 497), 137.3 parts by weight of polyethylene powder wax emulsion (W400), 7.5 parts by weight of thickener (EW-NA), and 1065.8 parts by weight of deionized water for 30 minutes until they were uniformly dispersed.
[0086] The aqueous hot melt adhesive solution was coated on a medical paper (PeltaMed PurePeelEO 60gsm) and dried at 100°C for 2 minutes to form an aqueous hot melt adhesive coating layer on the medical paper, thereby preparing an aqueous hot melt adhesive coating medical paper.
[0087] The obtained aqueous hot melt adhesive coating medical paper was subjected to air permeability test, heat seal strength test, and peel test according to the methods described below, and the test results are shown in Table 1 below.
[0088] Example 6
[0089] An aqueous hot melt adhesive solution was formed by mixing and stirring 233.3 parts by weight of ethylene-vinyl acetate copolymer latex (DA-104), 100 parts by weight of ethylene-acrylic acid copolymer latex (Novaseal 5132), 660 parts by weight of aqueous paraffin emulsion (Aquacer 497), 137.3 parts by weight of polyethylene powder wax emulsion (W400), 7.5 parts by weight of thickener (EW-NA), and 1065.8 parts by weight of deionized water for 30 minutes until they were uniformly dispersed.
[0090] The aqueous hot melt adhesive solution was coated on a medical paper (PeltaMed PurePeelEO 60gsm) and dried at 100°C for 2 minutes to form an aqueous hot melt adhesive coating layer on the medical paper, thereby preparing an aqueous hot melt adhesive coating medical paper.
[0091] The obtained aqueous hot melt adhesive coating medical paper was subjected to air permeability test, heat seal strength test, and peel test according to the methods described below, and the test results are shown in Table 1 below.
[0092] Example 7
[0093] An aqueous hot melt adhesive solution was formed by mixing and stirring 233.3 parts by weight of an ethylene-vinyl acetate copolymer latex (EP 707K), 100 parts by weight of an ethylene-acrylic acid copolymer latex (Novaseal 5132), 40.7 parts by weight of an aqueous paraffin emulsion (Aquacer 497), 51.3 parts by weight of a polyethylene powder wax emulsion (Wax 4), 2.9 parts by weight of a thickening agent (EW-NA), and 383.8 parts by weight of deionized water for 30 minutes to uniformly disperse them.
[0094] The aqueous hot melt adhesive solution was coated on a medical paper (PeltaMed PurePeelEO 60gsm) and dried at 100°C for 2 minutes to form an aqueous hot melt adhesive coating layer on the medical paper, thereby preparing an aqueous hot melt adhesive coating medical paper.
[0095] The obtained aqueous hot melt adhesive coating medical paper was subjected to air permeability test, heat seal strength test, and peel test according to the methods described below, and the test results are shown in Table 1 below.
[0096] Example 8
[0097] An aqueous hot melt adhesive solution was formed by mixing and stirring 233.3 parts by weight of an ethylene-vinyl acetate copolymer latex (DA-104), 100 parts by weight of an ethylene-acrylic acid copolymer latex (Novaseal 5132), 25.3 parts by weight of a polyethylene ionic polymer resin emulsion (S500), 40.7 parts by weight of an aqueous paraffin emulsion (Aquacer 497), 51.3 parts by weight of a polyethylene powder wax emulsion (W400), and 393.3 parts by weight of deionized water for 30 minutes to uniformly disperse them.
[0098] The aqueous hot melt adhesive solution was coated on a medical paper (PeltaMed PurePeelEO 60gsm) and dried at 100°C for 2 minutes to form an aqueous hot melt adhesive coating layer on the medical paper, thereby preparing an aqueous hot melt adhesive coating medical paper.
[0099] The obtained aqueous hot melt adhesive coating medical paper was subjected to air permeability test, heat seal strength test, and peel test according to the methods described below, and the test results are shown in Table 1 below.
[0100] Example 9
[0101] An aqueous hot melt adhesive solution was formed by mixing and stirring 233.3 parts by weight of ethylene-vinyl acetate copolymer latex (DA-104), 100 parts by weight of ethylene-acrylic acid copolymer latex (Novaseal 5132), 64.7 parts by weight of polyethylene ionic polymer resin emulsion (S500), 72 parts by weight of aqueous paraffin emulsion (Aquacer 497), 51.3 parts by weight of polyethylene powder wax emulsion (W400), 4.2 parts by weight of thickening agent (AS-1125), and 433.3 parts by weight of deionized water for 30 minutes to uniformly disperse them.
[0102] The aqueous hot melt adhesive solution was coated on a medical paper (PeltaMed PurePeelEO 60gsm) and dried at 100°C for 2 minutes to form an aqueous hot melt adhesive coating layer on the medical paper, thereby preparing an aqueous hot melt adhesive coating medical paper.
[0103] The obtained aqueous hot melt adhesive coating medical paper was subjected to air permeability test, heat seal strength test, and peel test according to the methods described below, and the test results are shown in Table 1 below.
[0104] Comparative Example 1
[0105] An aqueous hot melt adhesive solution was formed by mixing and stirring 233.3 parts by weight of ethylene-vinyl acetate copolymer latex (DA-104), 100 parts by weight of ethylene-acrylic acid copolymer latex (Novaseal 5132), 19.3 parts by weight of aqueous paraffin emulsion (Aquacer 497), 46.7 parts by weight of polyethylene powder wax emulsion (W400), 2.9 parts by weight of thickening agent (EW-NA), and 363.8 parts by weight of deionized water for 30 minutes to uniformly disperse them.
[0106] The aqueous hot melt adhesive solution was coated on a medical paper (PeltaMed PurePeelEO 60gsm) and dried at 100°C for 2 minutes to form an aqueous hot melt adhesive coating layer on the medical paper, thereby preparing an aqueous hot melt adhesive coating medical paper.
[0107] The obtained aqueous hot melt adhesive coating medical paper was subjected to air permeability test, heat seal strength test, and peel test according to the methods described below, and the test results are shown in Table 1 below.
[0108] Comparative Example 2
[0109] An aqueous hot melt adhesive solution was formed by mixing and stirring 233.3 parts by weight of an ethylene-vinyl acetate copolymer latex (DA-104), 100 parts by weight of an ethylene-acrylic acid copolymer latex (Novaseal 5132), 40.7 parts by weight of an aqueous paraffin emulsion (Aquacer 497), 51.3 parts by weight of a polyethylene powder wax emulsion (W410), 2.9 parts by weight of a thickening agent (EW-NA), and 370.4 parts by weight of deionized water for 30 minutes to uniformly disperse them.
[0110] The aqueous hot melt adhesive solution was applied to a medical paper (PeltaMed PurePeelEO 60 gsm), and dried at 100°C for 2 minutes to form an aqueous hot melt adhesive coating layer on the medical paper, thereby preparing an aqueous hot melt adhesive coating medical paper.
[0111] The obtained aqueous hot melt adhesive coating medical paper was subjected to air permeability test, heat seal strength test, and peel test according to the methods described below, and the test results are shown in Table 1 below.
[0112] Comparative Example 3
[0113] An aqueous hot melt adhesive solution was formed by mixing and stirring 473.3 parts by weight of a polyethylene ionic polymer resin emulsion (S300), 40.7 parts by weight of an aqueous paraffin emulsion (Aquacer 497), 51.3 parts by weight of a polyethylene powder wax emulsion (W400), and 260 parts by weight of deionized water for 30 minutes to uniformly disperse them.
[0114] The aqueous hot melt adhesive solution was applied to a medical paper (PeltaMed PurePeelEO 60 gsm), and dried at 100°C for 2 minutes to form an aqueous hot melt adhesive coating layer on the medical paper, thereby preparing an aqueous hot melt adhesive coating medical paper.
[0115] The obtained aqueous hot melt adhesive coating medical paper was subjected to air permeability test, heat seal strength test, and peel test according to the methods described below, and the test results are shown in Table 1 below.
[0116] The evaluation methods for coating weight measurement, air permeability test, heat seal strength test, and peel test are as follows:
[0117] Coating weight measurement: The coating weight of the aqueous hot melt adhesive was obtained by measuring the weights of the aforementioned aqueous hot melt adhesive coating medical paper and the medical paper before coating according to the test standards of EN ISO 536, respectively, and subtracting the weight of the medical paper from the weight of the aqueous hot melt adhesive coating medical paper, and the unit thereof was g / m 2 (gsm).
[0118] Air permeability test: The average seconds required for 100 cc of air to pass through the aforementioned water-based hot melt adhesive coated medical paper were measured using an air permeability tester (Model 4980-D, purchased from Lian Sheng Instrument) according to the test standard of TAPPI T-460.
[0119] Seal strength measurement: The polyethylene (PE) film and the aforementioned water-based hot melt adhesive coated medical paper were heat-pressed with a heat sealing tester (BS-25, purchased from Da Ba Jing Machine) at an area of 10 cm long and 1 cm wide. The upper plate temperature was set to 150 degrees Celsius, the lower plate temperature was set to room temperature, the heat sealing pressure was set to 5 kg, and the pressing time was set to 3.5 seconds. The maximum tensile force value, i.e. the seal strength, of the resulting heat-sealed product was measured using a tensile testing machine (AI-3000, purchased from Gao Tie Technology) according to the test standard of ASTM F-88.
[0120] Peeling test: The PE film in the aforementioned heat-sealed product was manually peeled off from the water-based hot melt adhesive coated medical paper, and the condition of fiber peeling on the medical paper after peeling was observed visually. If no fiber peeling was found on the surface of the medical paper, it was evaluated as 0, and if fiber peeling was found on the surface of the medical paper, it was evaluated as X.
[0121] Table 1: Coating weight, air permeability, heat seal strength and peeling test results of water-based hot melt adhesive coated medical paper of examples and comparative examples
[0122]
[0123]
[0124] As can be seen from Table 1, the water-based hot melt adhesive coated medical paper prepared in Examples 1 to 9 not only has good air permeability, but also has sufficient seal strength after heat sealing with the PE film, and the water-based hot melt adhesive layer is intermittently broken when the PE film is peeled off, thereby avoiding the problem of fiber detachment of the medical paper.
[0125] Although the present application has been disclosed as above with examples, it is not intended to limit the present application, and those skilled in the art should be able to make various changes and modifications without departing from the spirit and scope of the present application, therefore the protection scope of the present application shall be defined by the appended claims.
Claims
1. A water-based hot melt adhesive comprising: 25 to 70 parts by weight of ethylene-vinyl acetate copolymer; 5 to 20 parts by weight of ethylene-acrylic acid copolymer; 6.5 to 55 parts by weight of aqueous paraffin; and 5 to 15 parts by weight of powdered wax, wherein: The particle size of the powder wax is less than 8 microns.
2. The water-based hot melt adhesive according to claim 1, wherein the water-based hot melt adhesive comprises: 30 to 68 parts by weight of the ethylene-vinyl acetate copolymer; 6 parts by weight to 18 parts by weight of the ethylene-acrylic acid copolymer; 7 to 52 parts by weight of the aqueous paraffin; and 7 to 13 parts by weight of the powder wax. 3 . The water-based hot melt adhesive according to claim 1 , wherein the ratio of the weight of the powdered wax to the total weight of the ethylene-vinyl acetate copolymer and the ethylene-acrylic acid copolymer is 0.09 to 2.
1. 4 . The water-based hot melt adhesive according to claim 1 , wherein the ethylene-vinyl acetate copolymer has a glass transition temperature of -40° C. to 10° C. and a melting point of 200° C. to 300° C. The water-based hot melt adhesive according to claim 1 , wherein the ethylene-acrylic acid copolymer has a glass transition temperature of 0° C. to 10° C. and a melting point of 70° C. to 110° C. The water-based hot melt adhesive according to claim 1 , wherein the powdered wax has a glass transition temperature of less than 0° C. and a melting point of 70° C. to 180° C. 7 . The water-based hot melt adhesive according to claim 1 , wherein the wax powder is selected from the group consisting of Fischer-Tropsch synthesis wax powder, polypropylene wax powder, polyethylene wax powder, oxidized polyethylene wax powder, microcrystalline wax, and combinations thereof. The water-based hot melt adhesive according to claim 1 , wherein the particle size of the wax powder is 2 μm to 7 μm. 9 . The water-based hot melt adhesive according to claim 1 , wherein the water-based paraffin wax has a glass transition temperature of -120° C. to -50° C. and a melting point of 30° C. to 65° C. 10 . The water-based hot melt adhesive according to claim 1 , further comprising a water-based polyolefin resin, wherein the water-based polyolefin resin is a hydrophilically modified polyolefin, a water-based ionomer, or a combination thereof. The water-based hot melt adhesive according to claim 10 , further comprising 3 to 10 parts by weight of the water-based polyolefin resin.
12. The water-based hot melt adhesive according to claim 10, wherein the hydrophilically modified polyolefin is selected from the group consisting of hydrophilically modified polyethylene resin, hydrophilically modified polypropylene resin, hydrophilically modified polybutylene resin, hydrophilically modified oxidized polyethylene resin, and combinations thereof.
13. The water-based hot melt adhesive according to claim 10, wherein the water-based ionomer is selected from the group consisting of water-based polyethylene ionomer, water-based polypropylene ionomer, water-based polybutylene ionomer, water-based oxidized polyethylene ionomer, and combinations thereof. 14 . The water-based hot melt adhesive according to claim 10 , wherein the weight ratio of the water-based polyolefin resin to the water-based paraffin is 1:1 to 1:
3.
15. A water-based hot melt adhesive-coated medical paper, comprising medical paper and a water-based hot melt adhesive coating formed on at least one surface of the medical paper, wherein the water-based hot melt adhesive coating comprises: 25 to 70 parts by weight of ethylene-vinyl acetate copolymer; 5 to 20 parts by weight of ethylene-acrylic acid copolymer; 6.5 to 55 parts by weight of aqueous paraffin; and 5 to 15 parts by weight of powdered wax, wherein: The particle size of the powder wax is less than 8 microns.
16. The water-based hot melt adhesive coated medical paper according to claim 15, wherein the water-based hot melt adhesive coated medical paper has an air permeability of less than 600 seconds and a sealing strength greater than 300g / 15mm.
17. The water-based hot melt adhesive coated medical paper according to claim 15, wherein the coating amount of the water-based hot melt adhesive coating on the medical paper is 1 g / m 2 Up to 5g / m 2 .
Citation Information
Patent Citations
Porous and breathable coating hot-seal adhesive as well as preparation method and coating process thereof
CN108441149A
Waterborne coating hot-seal adhesive used for medical dialysis paper and coating process thereof
CN108587521A
Medical plastic uptake box hot-sealing cover material adhesive
CN110591602A
Cited By
Heat-sealing paper bag and preparation method thereof
CN121976429A